Effects of ellagitannin-rich berries on blood lipids, gut microbiota, and urolithin production in human subjects with symptoms of metabolic syndrome - Puupponen-Pimiä, Riitta; Seppänen-Laakso, Tuulikki; Kankainen, Matti; Maukonen, Johanna; Törrönen, Riitta; Kolehmainen, Marjukka; Leppänen, Tiina; Moilanen, Eeva; Nohynek, Liisa; Aura, Anna-Marja; Poutanen, Kaisa; Tómas-Barberán, Francisco A.; et al. (Molecular nutrition & food research, 2013)
Ellagitannins are polyphenols abundant in strawberries, raspberries, and cloudberries. The effects of a mixture of these berries were studied in a randomized controlled trial with subjects having symptoms of metabolic syndrome. The study focused on serum lipid profiles, gut microbiota, and ellagitannin metabolites. The results indicate that bioavailability of ellagitannins appears to be dependent on the composition of gut microbiota.